Oceanographic Data of the 34th Japanese Antarctic Research Expedition from November 1992 to March 1993 - ハシマ, タケヒコ; ナミキ, マサハル; HASHIMA, Takehiko; NAMIKI, Masaharu (National Institute of Polar Research, 1997)
P(論文) The results of oceanographic observations on board the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica are presented in this report. The oceanographic observations were carried out by the summer party of the 34th Japanese Antarctic Research Expedition (JARE-34) during the austral summer of 1992/1993. The tidal observations were carried out by the winter party of JARE-33 from February 1992 to January 1993. departmental bulletin paper